Cell-specific expression of the FAP gene is regulated by enhancer elements - Antonova, Dina V.; Gnatenko, Dmitry A.; Kotova, Elena S.; Pleshkan, Victor V.; Kuzmich, Alexey I.; Didych, Dmitry A.; Sverdlov, Eugene D.; Alekseenko, Irina V. (Frontiers in Molecular Biosciences, 2023)
Fibroblast activation protein (FAP) is an integral membrane serine protease that acts as both dipeptidyl peptidase and collagenase. In recent years, FAP has attracted considerable attention due to its specific upregulation in multiple types of tumor cell populations, including cancer cells in various cancer types, making FAP a potential target for therapy. However, relatively few papers pay attention to the mechanisms driving the cell-specific expression of the FAP gene. We found no correlation between the activities of the two FAP promoter variants (short and long) and the endogenous FAP mRNA expression level in several cell lines with different FAP expression levels. This suggested that other mechanisms may be responsible for specific transcriptional regulation of the FAP gene. We analyzed the distribution of known epigenetic and structural chromatin marks in FAP-positive and FAP-negative cell lines and identified two potential enhancer-like elements (E1 and E2) in the FAP gene locus. We confirmed the specific enrichment of H3K27ac in the putative enhancer regions in FAP-expressing cells. Both the elements exhibited enhancer activity independently of each other in the functional test by increasing the activity of the FAP promoter variants to a greater extent in FAP-expressing cell lines than in FAP-negative cell lines. The transcription factors AP-1, CEBPB, and STAT3 may be involved in FAP activation in the tumors. We hypothesized the existence of a positive feedback loop between FAP and STAT3, which may have implications for developing new approaches in cancer therapy.